Seismic simulation tools and methods appropriate for developing countries. (December 2021) - Bothara, Jitendra; Desai, Rajendra; Ingham, Jason; Dizhur, Dmytro
Abstract: Understanding the earthquake behavior of structures is the first step towards developing a strategy for earthquake-resilient design and construction of the built environment. The growing number of earthquake simulators (shake tables) globally has allowed researchers to closely study the response of different building types when subjected to simulated earthquake shaking. Typically, such simulators are sophisticated and complex testing apparatus that require high levels of skill and experience for their effective operation and are associated with high costs of installation, operation, maintenance, and repair. In developing countries where there is limited investment in research, the application of such tools to meet the current need for experimental campaigns is generally not feasible, and hence alternative tools and methods are sought. In this context, a detailed review into alternative cost-effective tools and methods such as shock tables, harmonic shake tables, and controlled underground explosions for experimental testing was undertaken and is reported herein. Furthermore, the design, detailing, and construction of a shock table and a harmonic shake table are presented.